Variations in Condom Use by Type of Partner in 13 Sub-Saharan African Countries - de Walque, Damien; Kline, Rachel (2012)
Using nationally representative data from 13 sub-Saharan African countries, we reinforce and expand upon previous findings that men report using condoms more frequently than women do and that unmarried respondents report that they use condoms with casual partners more frequently than married individuals report using them with their spouses. Based on descriptive, bivariate, and multivariate analyses, we also demonstrate to a degree not previously shown in the current literature that married men from most countries report using condoms with extramarital partners about as frequently as unmarried men report using them with casual partners. Married women from most of the countries included in the study reported using condoms with extramarital partners less frequently than unmarried women reported using them with casual partners. This result is especially troubling because marriage usually ensures regular sexual intercourse, thereby providing more opportunities for a person to pass HIV infection from an extramarital partner to his or her spouse. These findings about high-risk behaviors can be used to better target future HIV-transmission-prevention efforts.